2017
DOI: 10.2807/1560-7917.es.2017.22.35.30607
|View full text |Cite
|
Sign up to set email alerts
|

Environmental surveillance during an outbreak of tularaemia in hares, the Netherlands, 2015

Abstract: Tularaemia, a disease caused by the bacterium Francisella tularensis, is a re-emerging zoonosis in the Netherlands. After sporadic human and hare cases occurred in the period 2011 to 2014, a cluster of F. tularensis-infected hares was recognised in a region in the north of the Netherlands from February to May 2015. No human cases were identified, including after active case finding. Presence of F. tularensis was investigated in potential reservoirs and transmission routes, including common voles, arthropod vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In Hungary a hare (Lepus europaeus)-tick cycle explains their inter-epizootic period [22] and should be studied in Georgia. Contaminated water also is likely to serve as a reservoir [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In Hungary a hare (Lepus europaeus)-tick cycle explains their inter-epizootic period [22] and should be studied in Georgia. Contaminated water also is likely to serve as a reservoir [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Disease incidence due to infections with subspecies holarctica has been shown to be higher near lakes and rivers (Desvars et al, 2015 ). F. tularensis has been detected in various types of surface waters and sediments (Petersen et al, 2009 ; Broman et al, 2011 ; Janse et al, 2017 ) where the bacterium can be hosted by free-living protozoa and may reside in biofilms (Abd et al, 2003 ; Sinclair et al, 2008 ; van Hoek, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, occasional human cases (17 in total) have been reported. Also, after surveillance of dead hares started in 2011 (Janse et al, 2017 ), several Francisella -infected hares were identified in the same period. These human and hare tularemia cases from 2011 to 2017 occurred dispersed in time and space (van de Wetering et al, 2015 ; Pijnacker et al, 2016 ; Janse et al, 2017 ; Zijlstra et al, 2017 ), which suggests a widespread occurrence and the existence of an endemic cycle of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations